Long-term mechanical durability of dental nanocomposites containing amorphous calcium phosphate nanoparticles - Moreau, Jennifer L.; Weir, Michael D.; Giuseppetti, Anthony A.; Chow, Laurence C.; Antonucci, Joseph M.; Xu, Hockin H. K. (Journal of biomedical materials research. Part B, Applied biomaterials, 2012)
Half of all dental restorations fail within 10 years, with secondary caries and restoration fracture being the main reasons. Calcium phosphate (CaP) composites can release Ca and PO4 ions and remineralize tooth lesions. However, there has been no report on their long‐term mechanical durability. The objective of this study was to investigate the wear, thermal‐cycling, and water‐aging of composites containing amorphous calcium phosphate nanoparticles (NACP). NACP of 112‐nm and glass particles were used to fabricate four composites: (1) 0% NACP+75% glass; (2) 10% NACP+65% glass; (3) 15% NACP+60% glass; and (4) 20% NACP+50% glass. Flexural strength and elastic modulus of NACP nanocomposites were not degraded by thermal‐cycling. Wear depth increased with increasing NACP filler level. Wear depths of NACP nanocomposites after 4 × 105 cycles were within the range for commercial controls. Mechanical properties of all the tested materials decreased with water‐aging time. After 2 years, the strengths of NACP nanocomposites were moderately higher than the control composite, and much higher than the resin‐modified glass ionomers. The mechanism of strength loss for resin‐modified glass ionomer was identified as microcracking and air‐bubbles. NACP nanocomposites and control composite were generally free of microcracks and air‐bubbles. In conclusion, combining NACP nanoparticles with reinforcement glass particles resulted in novel nanocomposites with long‐term mechanical properties higher than those of commercial controls, and wear within the range of commercial controls. These strong long‐term properties, plus the Ca‐PO4 ion release and acid‐neutralization capability reported earlier, suggest that the new NACP nanocomposites may be promising for stress‐bearing and caries‐inhibiting restorations. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 2012.